2019
DOI: 10.1111/pcmr.12790
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of spectral distribution of a large cohort of Chinese patients with non‐syndromic oculocutaneous albinism facilitates genetic diagnosis

Abstract: Non‐syndromic oculocutaneous albinism (nsOCA) is a group of genetically heterogeneous autosomal recessive disorders with complete lack or decrease pigmentation in skin, hair, and eyes. TYR, OCA2, TYRP1, SLC45A2, SLC24A5, and LRMDA were reported to cause OCA1‐4 and OCA6‐7, respectively. By sequencing all the known nsOCA genes in 114 unrelated Chinese nsOCA patients combined with In silico analyses, splicing assay, and classification of variants according to the standards and guidelines of American College of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
(84 reference statements)
0
21
1
Order By: Relevance
“…However, researchers were unable to conclude the molecular diagnosis for approximately 27% of participants (Lasseaux et al, 2018). Another study reported 31 new mutations in a cohort of 114 individuals with albinism and also reported 14% participants without identified mutations (Zhong et al, 2019). Despite a smaller group of subjects, our study identified one novel mutation and two rare variants, as cause of OCA.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, researchers were unable to conclude the molecular diagnosis for approximately 27% of participants (Lasseaux et al, 2018). Another study reported 31 new mutations in a cohort of 114 individuals with albinism and also reported 14% participants without identified mutations (Zhong et al, 2019). Despite a smaller group of subjects, our study identified one novel mutation and two rare variants, as cause of OCA.…”
Section: Discussioncontrasting
confidence: 55%
“…In our cohort, the variant c389_391delAGA was identified in siblings (C6 and C7) whose ancestry analysis clustered them with Ad Mixed American instead of African population, this is in agreement with the TOPMed freeze 5 panel study. A second mutation, c.1037-7T > A, which was previously reported as causing OCA1 (Park et al, 1997;Grønskov et al, 2009;Lasseaux et al, 2018;Zhong et al, 2019), segregated in trans with c.389_391delAGA. Both mutations were identified in individuals (C6 and C7) who presented ophthalmologic manifestations and hair and skin hypopigmentation consistent with the albinism phenotype (Figure 1).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…OCA is a group of autosomal recessive disorders characterized by the loss of or a reduction in pigmentation in the eyes, hair, and skin. Populations of all ethnic backgrounds can be affected by OCA, with an estimated global prevalence of 1 : 17,000 [6][7][8][9]. Very rarely, OCA may be accompanied by systematic defects such as Hermansky-Pudlak and Chediak-Higashi syndromes [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that over 50% of OCA patients with molecular diagnosis have a mutation in TYR (OCA1) encoding tyrosinase while around 2-3% have a defective TYRP1 (OCA3) encoding tyrosinase related 1 protein 1,58 . Both enzymes are well known to control pigment synthesis 9 .…”
Section: Introductionmentioning
confidence: 99%